Magnetic Cloud Boundary Layers and Magnetic Reconnection - Wang, Yi (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This thesis focuses on magnetic reconnection processes in the boundary layer of the interplanetary magnetic cloud. Magnetic reconnection is an important and frontier topic in the realm of physics. Various physical phenomena can be observed during the reconnection process but lots of them are not fully understood. This thesis provides the first observational evidence of energetic electrons associated with magnetic reconnection in the solar wind and discusses the particle acceleration problems. In addition, after analyzing the particle flux variations in Magnetic Cloud Boundary Layer, the thesis proposes a possible new criterion for the identification of magnetic reconnection in the solar wind. These tantalizing results could be particular clues to understand the dynamical problems in magnetic reconnection processes.